GE_GERICHTE C/2607/2018 vom 29. Januar 2019 - GE Cour de justice (2019)
MAINLEVÉE PROVISOIRE; TITRE DE MAINLEVÉE ; RECONNAISSANCE DE DETTE ; ERREUR ESSENTIELLE ; TRANSACTION EXTRAJUDICIAIRE | LP.82; CO.23; CO.24.al1.ch3; CO.24.al1.ch4